Higher Education Instructor Perception of Helpfulness of Inclusive and Equitable Online Teaching Strategies - Martin, Florence; Oyarzun, Beth; Sadaf, Ayesha (Online Learning, 2023)
Online learners are increasingly diverse (NCES, 2022), which underlines the need for instructors to be inclusive and equitable in online teaching. Inclusion refers to providing opportunities for all learners in the online course, so they can actively participate and feel welcomed and belong in the course, and equity ensures that all learners have fair treatment and access to the opportunities and resources needed to succeed. In this survey-based research, we developed an Inclusive and Equitable Online Teaching Strategies (IEOTS) instrument with 45 strategies and examined instructor perceptions of the helpfulness of these strategies. These strategies focused on instructor self-awareness and commitment, getting to know the learners, course design, course facilitation, and evaluation. Based on the 478 online instructor survey responses, descriptive statistics showed that the instructors rated the strategies between somewhat helpful and helpful. In the open-ended question, student choice was described as an important aspect of the online course being inclusive and equitable. Analysis conducted based on the learner (student level), instructor (gender, ethnicity, teaching experience and teaching expertise), course (delivery modality), and organizational differences (required training, collaboration with instructional designer) found that instructor perceptions of helpfulness was higher for the course design subscale for instructors who taught online asynchronously rather than synchronously; higher for the know your learner subscale for instructors who taught graduate students rather than those who taught undergraduate students, and between those who attended training for online teaching compared to those who had not. In addition to supporting diverse online students, this study has implications for online instructors, instructional designers, and administrators who provide support to integrate these strategies effectively.